JAMALUDDIN AL-AFGHANI: PAN-ISLAMISM AND TRACES OF HIS THOUGHTS IN INDONESIA - Arifal Dzunuren; Junizar Suratman (Universitas Islam Negeri Imam Bonjol Padang, 2023)
This article discusses the work of Jamaluddin al-Afghani in the development of Islamic civilization, especially in the phase of Islamic renewal (XIX century). This paper is intended to re-read how the struggle of Jamaluddin al-Afghani's thought, with its culmination of Pan-Islamism, and its effects on the development of thought in Indonesia. Studies are based on libraries research by collecting, discussing ,and analyzing related literature on the focus of the study theme. Jamaluddin al-Afghani's long journey across the countries of the world, both in the east and west, witnessed his struggle and thinking, to give birth to the idea of unity so that the people as a way to be free from the grasp of western colonization, known as Pan-Islamism. This idea has not yet been found a concrete concept, because the ideas of Pan-Islamism are widely contained in Jamaluddin's writings in al-Urwatul Wutsqa magazine. The influence of Jamaluddin al-Afghani's thinking also had an impact on the development of educational institutions in Indonesia, Jami'at Al-Khairat and Muhammadiyah became institutions that represented this work.